Table of contents (Journal of Irish Urban Studies, Vol.1 (No. 1), 2002) - (:unkn) unknown (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2002)
Table of contents
Keywords: Urban geography -- Ireland